EFEKTIFITAS PENGGUNAAN DIATOM DAN Brachionus plicatilis PADA PAKAN LARVA BANDENG - Abdul Muqsith (Faculty of Science and Technology University Ibrahimy, 2013)
The purpose of this study was to determine the effectiveness of the use of feed on diatoms and Brachionus plicatilis larvae feed banding, implemented Brackish Water Aquaculture Centres Situbondo July-August 2012. Research using five treatments and two replications that use Phaeodactylum sp, Chaetoceros sp, Nannochloropsis sp (as a control), Isocrysis sp, Pavlova sp. The results showed that after the larval rearing of milkfish for 21 days, the larvae length measurement data obtained highest in treatment C is 2.51 ± 0.1131 cm followed treatment D = 2.505 ± 0.1768 cm, treatment E = 2.29 ± 0.990 cm, treatment B = 2.245 ± 0.1061 cm and treatment A was 2.17 ± 0.0849 cm. While weight gain during maintenance milkfish larvae highest at C treatment amounting to 0.0782 ± 0.0050 grams followed by treatment D = 0.0712 ± 0.0028 grams, E = 0.0670 ± 0.0032 grams, B = 0.0639 ± 0.0023 grams and final treatment A of 0.0610 ± 0.0113 grams. The highest daily growth rate in the treatment of C = 0.00397 grams/day, followed by treatment D = 0.00394 grams/day, treatment B = 0.00354 grams/day, treatment A = 0.00335 grams/day and treatment E = 0.00273 grams/day. Hatching rate not so good and in the range of 60%, but in treatment C (treatment Nannochloropsis sp) achieved the highest level of magnitude that is equal to 52.80% and then followed treatment D, E, B and A.